Global trends and epidemiological impact of metabolic risk factors on atrial fibrillation and atrial flutter from 1990 to 2021 - Junqing Liang; Jun Shen; Yankai Guo; Manzeremu Rejiepu; Xiuwen Ling; Xiaoyan Wang; Yi Jian; Xing Zhang; Shijie Shao; Baopeng Tang; Ling Zhang (Scientific Reports)
Abstract Atrial fibrillation (AF) and atrial flutter (AFL) are cardiac arrhythmias associated with high morbidity and mortality. This cross-sectional observational study assesses the epidemiological burden of AF/AFL concerning metabolic risk factors using the Global Burden of Disease (GBD) 2021 database. Age-standardized disability-adjusted life years rate (ASDR), mortality, and estimated annual percentage change were calculated. The Bayesian Age-Period-Cohort model was utilized to predict future trends in ASDR and age-standardized mortality rate (ASMR) for AF/AFL 2030. Between 1990 and 2021, ASDR rose from 34.22 to 34.94, whereas ASMR increased from 1.46 to 1.50 per 100,000 people. High/high–middle Socio-Demographic Index (SDI) regions showed decreasing trends in ASDR and ASMR, whereas low and middle SDI regions showed increasing trends. In 2021, the highest ASDR and ASMR were recorded in Australasia, North America, and Western Europe, with significant country-level variability. Projections indicate a declining trend in ASMR and stable ASDR through 2030. The global rise in AF/AFL attributable to metabolic risk factors necessitates comprehensive and region-specific public health strategies. Further research is warranted to develop and implement effective measures to mitigate these conditions and improve cardiovascular health outcomes worldwide.